Aberrant Expression of Breast Development-Related MicroRNAs, miR-22, miR-132, and miR-212, in Breast Tumor Tissues - Damavandi, Zahra (J Breast Cancer, 2016)
PURPOSE: MicroRNAs (miRNAs) are a major class of small endogenous RNA molecules that posttranscriptionally regulate the expression of most genes in the human genome. miRNAs are often located in chromosomal fragile sites, which are suscept-ible to amplification or deletion. Chromosomal deletions are frequent events in breast cancer cells. Deletion and loss of heterozygosity at 17p13.3 have been reported in 49% of breast cancers. The aim of the current study was to evaluate potential expression alterations of miR-22, miR-132, and miR-212, which are located on the 17p13.3 locus and are required for mammary gland development. METHODS: A matched case-control study was conducted, which included 36 pairs of tumor and matched nontumor surgical specimens from patients diagnosed with breast invasive ductal carcinoma. Formalin-fixed paraffin-embedded samples from archival collections at the pathology department of Shariati Hospital were prepared for RNA extraction using the xylene-ethanol method before total RNA was isolated with TRIzol Reagent. Specific primers were designed for cDNA synthesis and miRNA amplification. The expression of miRNAs was then evaluated by real-time polymerase chain reaction (RT-PCR). RESULTS: According to our RT-PCR data, the miR-212/miR-132 family was downregulated in breast cancer (0.328-fold, p<0.001), and this reduced expression was the most prominent in high-grade tumors. In contrast, miR-22 exhibited a significant upregulation in breast tumor samples (2.183-fold, p=0.040). CONCLUSION: Consistent with the frequent deletion of the 17p13.3 locus in breast tumor cells, our gene expression data demonstrated a significant downregulation of miR-212 and miR-132 in breast cancer tissues. In contrast, we observed a significant upregulation of miR-22 in breast tumor samples. The latter conflicting result may have been due to the upregulation of miR-22 in stromal/cancer-associated fibroblasts, rather than in the tumor cells.